Understanding the Interplay of Transport‐Morphology‐Performance in PBDB‐T‐Based Polymer Solar Cells. Issue 4 (29th January 2020) - Zhang, Qilin; Yuan, Xin; Feng, Yifeng; Larson, Bryon W.; Su, Gregory M.; Maung Maung, Yin; Rujisamphan, Nopporn; Li, Youyong; Yuan, Jianyu; Ma, Wanli
Abstract : Polymer–polymer blends have been reported to exhibit exceptional thermal and ambient stability. However, power conversion efficiencies (PCEs) from devices using polymeric acceptors have been recorded to be significantly lower than those based on conjugated molecular acceptors. Herein, two organic nonfullerene bulk heterojunction (BHJ) blends ITIC:PBDB‐T and N2200:PBDB‐T, together with their fullerene counterpart, PCBM:PBDB‐T, are adopted to understand the effect of electron acceptors on device performance. Free charge carrier properties using time‐resolved microwave conductivity (TRMC) measurements are comprehensively investigated. The nonfullerene devices show an improved PCE of 10.06% and 6.65% in the ITIC‐ and N2200‐based cells, respectively. In comparison, the PCBM:PBDB‐T‐based devices yield a PCE of 5.88%. The optimal N2200:PBDB‐T produced the highest TRMC mobility, longest lifetime, and greatest free‐carrier diffusion length. It is found that such phenomena can be associated with the unfavorable morphology of the all‐polymer BHJ microstructure. In contrast, the solar cells using either the PCBM or ITIC acceptors display a more balanced donor and acceptor phase separation, leading to more efficient free‐carrier separation and transport in the operating device. By sacrificing efficiency for superior stability, it is shown that the improved structure in all‐polymer blend can deliver a more stable morphology under thermal stress. Abstract : Through time‐resolved microwave conductivity measurements, the local intrinsic free‐carrier properties in three representative organic bulk heterojunction blends are comparatively investigated, and it is believed that the results shown here are important in understanding and improving the efficiency and stability of organic solar cells.